2011
DOI: 10.1186/1472-6963-11-308
|View full text |Cite|
|
Sign up to set email alerts
|

What stops children with a chronic illness accessing health care: a mixed methods study in children with Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME)

Abstract: BackgroundPaediatric Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) is relatively common and disabling with a mean time out of school of more than one academic year. NICE guidelines recommend referral to specialist services immediately if severely affected, within 3 months if moderately affected and within 6 months if mildly affected. However, the median time-to-assessment by a specialist service in the UK is 18 months. This study used a mixed-methods approach to examine factors associated with ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 23 publications
(33 reference statements)
0
40
2
Order By: Relevance
“…34 Previous literature has shown that delays in diagnosis of CFS and absenteeism because of CFS in adolescents are unfortunately (still) substantial. 10,35 FITNET treatment supported quick improvement of school attendance and thereby contributed to diminishing these detrimental effects of school absence during this critical time.…”
Section: Discussionmentioning
confidence: 97%
“…34 Previous literature has shown that delays in diagnosis of CFS and absenteeism because of CFS in adolescents are unfortunately (still) substantial. 10,35 FITNET treatment supported quick improvement of school attendance and thereby contributed to diminishing these detrimental effects of school absence during this critical time.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is particularly true for children from disadvantaged backgrounds because families that experience early family adversity may be less likely to overcome barriers to accessing specialist care. 15 …”
Section: Discussionmentioning
confidence: 99%
“…8,9,11 Although clinician-verified CFS seems to be less prevalent (0.1%-0.5%), [12][13][14] this discrepancy is almost certainly a consequence of referral pathways and barriers to accessing clinical services. 15 Recognition of CFS as a relatively common, highly debilitating, and potentially longterm pediatric disease has grown in recent years, 16,17 but it is important that the uncertainties regarding the population prevalence of pediatric CFS are resolved.…”
mentioning
confidence: 99%
“…We are unaware that this has been described previously. Historically, CFS/ME has been an illness surrounded by controversy and adolescents with CFS/ME experienced disbelief from others and feared judgement regarding their illness (Jelbert et al, 2010; Webb et al, 2011) The diagnosis can be stigmatising partly due to the poor understanding of the aetiology (Asbring & Narvanen, 2002), and families may develop strategies to protect themselves from judgement, blame or disbelief and to portray the severity of CFS/ME (Guise, Widdicombe, & McKinlay, 2007). Alternatively, comparisons to pre-CFS/ME may be triggered by a grief process, whereby families reflect on how simple and enjoyable eating used to be.…”
Section: Discussionmentioning
confidence: 99%